2007
DOI: 10.1167/iovs.06-1362
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Intravitreal Voriconazole

Abstract: Vitreous concentrations achieved during the first 8 hours were greater than the previously reported minimum inhibitory concentrations (MICs) of organisms most involved in fungal endophthalmitis. A rapid decline of intravitreal concentration suggests that supplementation of intraocular voriconazole to maintain therapeutic levels may therefore be required in clinical settings. Further studies are needed to determine the elimination rate of voriconazole after intravitreal injection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 25 publications
1
36
0
2
Order By: Relevance
“…Voriconazole is a triazole that has a broad spectrum of antifungal activities (18,21,30). The antifungal activity arises from a complex multimechanistic process initiated by the inhibition of a cytochrome P450 involved in the biosynthesis of ergosterol, namely, CYP51, which catalyzes the oxidative removal of the 14␣-methyl group of lanosterol or eburicol (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Voriconazole is a triazole that has a broad spectrum of antifungal activities (18,21,30). The antifungal activity arises from a complex multimechanistic process initiated by the inhibition of a cytochrome P450 involved in the biosynthesis of ergosterol, namely, CYP51, which catalyzes the oxidative removal of the 14␣-methyl group of lanosterol or eburicol (9).…”
mentioning
confidence: 99%
“…The antifungal activity arises from a complex multimechanistic process initiated by the inhibition of a cytochrome P450 involved in the biosynthesis of ergosterol, namely, CYP51, which catalyzes the oxidative removal of the 14␣-methyl group of lanosterol or eburicol (9). This eventually causes depletion of ergosterol and disrupts the integrity and function of fungal cell membranes, eventually leading to cell lysis (10,30). This antifungal agent is a synthetic derivative of fluconazole modified by adding a methyl group to the propyl backbone and by substituting a triazole moiety with a fluoropyrimidine group; this results in a higher affinity for fungal 14-␣-demethylase, leading to more potent activities and excellent efficacy in patients with a wide range of ocular fungal infections (8,9,13,28,34).…”
mentioning
confidence: 99%
“…Voriconazole shows 96% bioavailability after oral administration, and reaches a therapeutic level in the vitreous and aqueous in non-inflamed human eyes (8) . The intravitreal concentration of voriconazole in rabbits exhibited exponential decay time with a half-life of 2.5 hours, reaching undetectable levels after 8 hours (9) . Despite the reports of therapeutic success with oral (10) or intravitreal (9) voriconazole use, in the case described there was no improvement in the condition after the injection with voriconazole, which may be justified by the fact that a single injection was made, and not the daily doses until the lesion remission, as recommended (11) , with surgical treatment with posterior vitrectomy via pars plana being the option.…”
Section: Discussionmentioning
confidence: 97%
“…The intravitreal concentration of voriconazole in rabbits exhibited exponential decay time with a half-life of 2.5 hours, reaching undetectable levels after 8 hours (9) . Despite the reports of therapeutic success with oral (10) or intravitreal (9) voriconazole use, in the case described there was no improvement in the condition after the injection with voriconazole, which may be justified by the fact that a single injection was made, and not the daily doses until the lesion remission, as recommended (11) , with surgical treatment with posterior vitrectomy via pars plana being the option. It was also taken into account for the indication of the surgical procedure the fact of the bilateral visual impairment, which could assure a fast improvement of the VA with the surgery and, consequently, a better quality of life for the patient, besides her good general condition to undergo general anesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…Although previous studies have shown voriconazole to have a broad spectrum of activity and to be effective as primary therapy in the treatment of invasive aspergillosis, 50 g/ml of intravitreal voriconazole has been found to cause small foci of retinal necrosis in animal studies (9)(10)(11). Moreover, voriconazole has a relatively rapid elimination rate in the vitreous, and supplementary injection is frequently required in clinical treatment (12,13). Systemically administered voriconazole which would be given simultaneously with intravitreal injection would penetrate into the vitreous.…”
mentioning
confidence: 99%